Late presentation of adenovirus-induced hemorrhagic cystitis and ureteral obstruction in a kidney-pancreas transplant recipient - Klein, Jeffrey (Proc (Bayl Univ Med Cent), 2015)
We report a late presentation of adenovirus-induced renal allograft and bladder infection causing azotemia and hemorrhagic cystitis in a patient 5 years after simultaneous kidney-pancreas transplantation. Adenovirus has been increasingly recognized as a cause of morbidity and mortality in both solid organ and stem cell transplant recipients. We wish to emphasize the importance of early detection, as treatment options involve reduction of immunosuppression, followed by the addition of antiviral agents and supportive care.